In Situ Generation of Zinc Oxide Nanobushes on Microneedles as Antibacterial Coating. (April 2019) - Chew, Sharon W. T.; Zeng, Yongpeng; Cui, Mingyue; Chang, Hao; Zheng, Mengjia; Wei, Shi; Zhao, Wenting; Xu, Chenjie
This paper introduces a facile and scalable method to generate a layer of antibacterial coating on microneedles. The antibacterial coating (i.e., zinc oxide nanobushes) is generated on the surface of gold-coated polystyrene microneedles using the hydrothermal growth method. The antimicrobial property is examined using the agar diffusion test with both gram-positive and gram-negative bacteria.